1984
DOI: 10.1029/jb089ib06p04520
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity and tectonics of the Rivera Plate and implications for the 1932 Jalisco, Mexico, earthquake

Abstract: Seismicity on and near the boundaries of the Rivera plate is examined in order to determine the subduction regime of the Rivera plate and its influence on the earthquake behavior of the northernmost section of the mid‐America trench. In particular, we address the question of a Rivera‐Cocos boundary.There have been several large historic earthquakes in the coastal areas of the Mexican states Colima and Jalisco, but the last large event was in June 1932 (the 1932 Jalisco earthquake, Ms = 8.1). The present quiesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 28 publications
2
55
0
2
Order By: Relevance
“…On the basis of the occurrence of two strike-slip earthquakes just northwest of the Manzanillo trough (Figure 8b), Eissler and McNally [1984] propose that Rivera-Cocos motion is accommodated via left-lateral motion along a north trending fault zone. A recent series of offshore strike-slip earthquakes that were triggered by the October 9, 1995, Manzanillo earthquake strongly supports such a model.…”
Section: Rivera-cocosmentioning
confidence: 99%
“…On the basis of the occurrence of two strike-slip earthquakes just northwest of the Manzanillo trough (Figure 8b), Eissler and McNally [1984] propose that Rivera-Cocos motion is accommodated via left-lateral motion along a north trending fault zone. A recent series of offshore strike-slip earthquakes that were triggered by the October 9, 1995, Manzanillo earthquake strongly supports such a model.…”
Section: Rivera-cocosmentioning
confidence: 99%
“…Para el estudio se han tenido en consideración, además de los trabajos anteriormente mencionados, los siguientes resultados: Aguirre et al (2005); Allan (1986); Álvarez (2007); Barrientos et al (2006); Barrier et al (1998);Blackwell y Richards (2004); Bourgois y Michaud (2004); Campa (1978); Campa y Coney (1983) ;Chulick Mooney (2002); Courboulex et al (1997); Demant (1984); DeMets (2001); DeMets y Traylen (2000); Ego y Anson (2002); Eissler y McNally (1984); Ferrari et al (2012Ferrari et al ( , 1992; Figueroa (1970); García y Suárez (1996); Gutiérrez et al (2015); Guzmán et al (1989); Hubp et al (1985); Instituto Nacional de Estadística, Geografía e Informática (2005A); Kostoglodov y Bandy (1995); Kostoglodov y Pacheco (1999) ;López Ramos (1983); Hubp (1990); Hubp y Ortiz (1980); Manea et al (2005Manea et al ( , 2003Manea et al ( , 2002; Medina (1997); Meschede y Barckhausen (2000); Moore y Buffington (1968); Morán (1984); Nieto Samaniego et al (2005Samaniego et al ( , 1995; Nixon (1982); Núñez Cornú et al (2016); Ortiz Pérez y Boceo (1989); O...…”
Section: Características Geológicas Y De La Sismicidadunclassified
“…EISSLER and MCNALLY (1984) and SINGH et al (1985) suggested a dip angle of 20°for the interface between the Rivera and North American Plates. NÚ Ñ EZ-CORNÚ and SÁ NCHEZ-MORA (1999), reported a dip angle of 12°as estimated from local seismicity data, and similar values were obtained from reflection-refraction studies carried out in the central and northern regions of the Jalisco coast (DAÑ OBEITIA et al, 1997).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…More controversial are the geometry of the interface and the relative motion between the Rivera and Cocos Plates. Does the interface lie under the CRZ (NIXON, 1982) or further north (EISSLER and MCNALLY, 1984)? Is it a convergent (DEMETS and STEIN, 1990) or divergent (BANDY, 1992) boundary?…”
Section: Tectonic Settingmentioning
confidence: 99%